Revision del genero chileno Ptyophis (Scarabaeidae: Mololonthinae: Macrodactylini) - Mondaca, J.=700 1 Ocampo, F.
(Es, En)
Ilus., 23 ref.
Keywords: SCARABAEIDAE; INSECTA; TAXONOMIA; CHILE; PACHYDEMINI; TANYPROCTINI; TETRAPHYLLUS